3x2-9x/2x-6=0

Simple and best practice solution for 3x2-9x/2x-6=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x2-9x/2x-6=0 equation:



3x^2-9x/2x-6=0
Domain of the equation: 2x!=0
x!=0/2
x!=0
x∈R
We multiply all the terms by the denominator
3x^2*2x-9x-6*2x=0
Wy multiply elements
6x^3-9x-12x=0
We do not support expression: x^3

See similar equations:

| 2+7(b+1)=6b-9 | | 3x−12=2 | | 19+x=126 | | 7n÷5=2 | | 9x+4=3x9 | | 12x-1+12=40 | | 5(3x−3)=3(8x−2) | | -4+2*x=8-4*(2-x) | | 3*x+7=(2*x-5)+x)-2 | | y=2(0)^3-4(0)^2+3 | | 2(x-1)=(x+2) | | 6.2g+10=2.2g+22 | | (x-2)=3x+2 | | 5·x-9=31 | | 6p^2-24=0 | | -4(6+x)=-12 | | 1.2=t/1.5 | | 8p+4=100 | | -8+13x^2=0 | | 126x=69 | | 6y-8=0 | | 40+x=x-4(x-6) | | X-20=2x-35 | | -13+8n=2(-4+3n)-9 | | -6+7n=7(1+2n)-6 | | 4y-6y+y=-21 | | -9x+45=9(-7-3x)+6x | | -46-2p=-5(p+6)-4 | | 7+n=7(1-10n)+9n | | -40-8x=-10(x+2)-4 | | -9y-4y=26 | | -3-6(-4k-10)=-18-k |

Equations solver categories